Hubungan Kreativitas Belajar dengan Prestasi Belajar Siswa Kelas V Gugus XVI Kecamatan Liliriaja Kabupaten Soppeng - Abd Hafid; Sri Asirrah; Sudirman Sudirman; Muhammad Amran (STKIP Andi Matappa Pangkep, 2022)
The problem in this study is the lack of students' ability to develop answers or not being able to think creatively, tend to have poor learning achievements. However, it is possible for students who have high creativity to have good learning achievements, while students who have low creativity have high and low learning achievements. This study is a quantitative study with a correlation design that aims to determine the relationship between the implementation of creativity and the learning achievement of class V Cluster XVI students, Liliriaja District, Soppeng Regency. The results showed that there was a significant relationship between learning creativity and student achievement in class V Cluster XVI, Liliriaja District, Soppeng Regency with a tcount value (5.7855) greater (>) ttable value (1.66792) which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that learning creativity will have an impact on students' learning habits in learning so that it will affect their learning achievement in the classroom. So the better the learning creativity, the better student achievement will be. From these conclusions, the impact of this research is that good learning creativity will increase student achievement.